Exploring influential factors in hiring freelancers in online labor platforms: An empirical study - Jie Ren; Viju Raghupathi; Wullianallur Raghupathi (Economies, 2023)
Sharing economy online labor platforms play a critical role in bringing together freelancers and potential employers. This research is one of the few studies to address how freelancers' characteristics impact the likelihood of being hired by employers using the theory of person-environment fit as a broad framework. Using Freelancer data, this research investigates if country of residence (of a freelancer and the employer), amount earned, and time since registered on the platform, are associated with the employment decision. The results indicate that country of residence does matter. Freelancers who tend to be from the same country as the employers are more likely to be hired. Likewise, high-income freelancers are less likely to be hired. Further, being longer on the platform influences the association between income level and likelihood of being hired. Greater efforts should be made to eliminate the asymmetric information between freelancers and employers and to provide more opportunities for both parties. The operators of online labor platforms should be encouraged to display information about freelancers that relates to country of origin, along with reviews, ratings, and rates earned in the same skill category, which would have strategic implications for freelance entrepreneurs on how to leverage themselves on a shared-economy-based online labor platform.
Keywords: 330; freelancing; gig economy; labor-based platform; online labor market; P-E fit theory; sharing economy